Development of Adobe-Flash Based Interactive Multimedia on Viruses for Class X Students at SMAN 2 Sawahlunto - Anggya Sukmarindra; Ardi Ardi (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2022)
Based on the results of the questionnaire distributed to students and teachers at SMAN 2 Sawahlunto, it was found that the biological material that is considered difficult is virus material. The cause of the difficulties experienced by students is the material that is abstract and the language of the book used is difficult to understand. The media used in schools are PowerPoint and LKPD (student worksheets), but students still need other media to be able to help students understand virus material well. The purpose of this research is to produce interactive multimedia based on adobe flash that is valid and practical. This type of research is development research using 3 stages of the 4D development model, namely the definition stage, the design stage, and the development stage. The subjects of this study consisted of two biology lecturers, FMIPA UNP, and 1 biology teacher at SMAN 2 Sawahlunto as validators and practicalities by 30 students and 1 biology teacher at SMAN 2 Sawahlunto. Based on the research conducted, the resulting product is in the form of interactive multimedia based on Adobe Flash about virus material for class X SMA. The results of the validity test show that the interactive multimedia produced is valid with an average value of 85.41% and practicality results with an average value of 92.18% by teachers and 86.84% by students, so both are categorized as very practical. Based on this, it can be concluded that the developed interactive multimedia is valid and practical.